Laryngeal lesion in leprosy and the risk of aspiration - Bretan, Onivaldo [UNESP]; De Souza, Lucijane B.; Lastoria, Joel Carlos [UNESP] (Lepra, 2007)
Leprosy affects the larynx, damaging its mucosa and sensory nerves and loss of sensation may result in aspiration of food and secretions. The laryngeal lesion may be insidious. Post-mortem studies showed bronchopneumonia that could have originated from aspiration. In patients with laryngeal symptoms, dysphagia or aspiration pneumonia loss of laryngeal sensation should be looked for.